The Effect of a Health Education Video on Self-Efficacy in Preventing Transmission of Tuberculosis - Lucya, Vita; Nuryanti, Yuki (KnE Life Sciences, 2022)
Indonesia is one of the countries where the number of tuberculosis cases is still high; in 2019, there were 109,463 cases. The highest number of cases is in West Java. The city of Bandung is one of the cities with the highest cases; in 2019 there were 477 cases at the UPT Garuda City Health Center in Bandung and in 2020 there were 197. Self-efficacy can influence the prevention of tuberculosis. The purpose of this study was to determine the effect of a health education video on self-efficacy in preventing transmission of tuberculosis. This was a quasi-experimental study with a two-group pretest-posttest design. The sample consisted of 60 tuberculosis patients at the UPT Garuda City Health Center in Bandung, recruited using convenience sampling. Data were collected using a self-efficacy questionnaire. The differences in the self-efficacy scores and the effect of the health education video were analyzed using the paired t-test and ANCOVA. The results of this study indicated that the health education video had an effect on increasing self-efficacy in patients with mean square = 3360,017, f = 434,840, p-value < 0.001. The video helped the tuberculosis patients to understand how to prevent tuberculosis transmission. It is hoped that there will be additional innovations in the health sector that can help nursing services to prevent tuberculosis transmission, including through health education videos. Keywords: self-efficacy, tuberculosis, video